Agrobiodiversité et pratiques agricoles dans le pays Jbala (Tafza et Bellota) - Alexandrine Barontini (Revue d'ethnoécologie, 2017)
The Jbala region is located mostly on the western and central Rif’s mountain chain, from the Straits of Gibraltar to, south, the Ouergha (without the atlantic plains and plateau). It is a mountain area, inhabited by a rural and quite dense population, whose principal economic activity is agriculture. A traditional agriculture mostly characterised by the use of a subsistence mixed farming as part of a agro-sylvo-pastoral system of production which constitutes specific landscapes. Physical, natural, socio-economic and historic particularities created favorable conditions maintaining several rare cultivated plants and practices.Thanks to the international scientific cooperation project (PICS) « La Montagne et ses Savoirs », we have collected (between October 2013 and April 2014) a series of interviews with farmers, merchants or inhabitants of the region, in two sites: Tafza and Bellota.We present here the results of a modest comparison between the agro-biological diversity and the linguistic diversity, through some of the vernacular taxinomy concerning fruits and fruit trees.